Breast Self-Examination Self-Efficacy Scale: Translation and Validation in Pakistani (Urdu) Version - Sumaira Naz; Sureeporn Thanasilp; Wasinee Wisesrith (Medsci Publications, 2024)
Introduction: There is a necessity of Pakistani (Urdu) translation and validation of Breast self-examination (BSE) self-efficacy scale to access high- risk women confidence in doing self-examination of breast as screening measures. The study aim is to translate and validate breast self-examination self-efficacy scale in Pakistani high-risk women. Methodology: The 12 items BSE Self-Efficacy scale was translated and validated by using Brislin (1970) and Sperber (2004) methodology. Psychometric properties of Pakistan version BSE Self-Efficacy scale were assessed among 120 women from oncology department of the tertiary care hospital in Pakistan selected with simple random sampling. CFA (Confirmatory factor analysis) was done for measuring the construct validity and reliability was assessed by Cronbach alpha coefficient. Demographics characteristics were analysed by descriptive statistics with SPSS and Mplus software was used for CFA. Results: The translated version showed semantic equivalence to the original English version. CFA results indicated that all 12 items were consistent with a unidimensional scale (χ2=464.3, p > .05, df=54, RMSEA =.025, CFI=.965, TLI=.913, SRMR=.062), Cronbach's α value .96, demonstrating high reliability. Conclusion: The twelve-item BSE self-efficacy scale Pakistani version established appropriate translation, validity and reliability in measuring confidence of doing BSE.